Experimental analyses of sexual and natural selection on short tails in a polygynous warbler. - Balmford, A; Lewis, M; Brooke, M; Thomas, A; Johnson, C (2000)
We believe that no experimental study has yet tested Darwin's idea that, as well as generating trait elaboration, intersexual selection might sometimes drive sex-biased trait reduction. Here we present the results of two experiments exploring the negative relationship between tail length and reproductive success in male golden-headed cisticolas (Cisticola exilis). In the first experiment, artificially shortening a male's tail produced a dramatic increase in his reproductive success, measured as either the number of females nesting or number of chicks Hedged on his territory. A second experiment, in which manipulated birds were flown through a maze, revealed that short tails also impose costs by reducing aerodynamic performance during slow-speed foraging flight. Because tail shortening yields reproductive benefits and viability costs, we conclude it has evolved via sexual selection. Disentangling exactly how short tails enhance male reproductive success is more difficult. Male-male competition appears partly responsible: aerodynamic theory predicts that tail reduction enhances high-speed flight and, in line with this, shortened-tail males spent more time engaged in high-speed aerial chases of rivals and defended higher-quality territories. However, shortened-tail males had higher reproductive success independent of territory quality and spent more time in aerial displays which may be directed at females. This suggests that tail shortening is also favoured via female choice based on male phenotype.